ANALISIS PENGARUH STRES KERJA, URAIAN PEKERJAAN, DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI APARATUR SIPIL NEGARA DINAS PERHUBUNGAN PROVINSI MALUKU - Jonathan Saily (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2017)
The role of an organization or institution must have a reliable quality ofhuman resources in playing its role to move the organization or institution in thecontext of development, of course the main impact of that role is the resultingperformance. In the form of performance as one of the goals in exploring thevarious skills or abilities possessed to be able to run a wheel organization eitherindividual or institution. The purpose of this study is to know and analyze theeffect of job stress, job description, job satisfaction on employee performance.The research method used is survey and explanatory research method to analyzethe relationship between variables studied. Analytical test tool used in thisresearch is using multiple regression analysis.The hypothesis was tested by using F test, and t test, the result showed that(1) job stress significantly or significantly affect the performance of State CivilApparatus; (2) job description significantly or significantly affect the performanceof the State Civil Apparatus; (4) job stress, job description, and satisfactiontogether (simultaneously) have real or significant effect on the performance ofcivil servant apparatus employees. There are several implications that can besuggested in this study.